Concurrent overactivation of the cytosolic glutamine synthetase and the GABA shunt in the ABA-deficient sitiens mutant of tomato leads to resistance against Botrytis cinerea - Seifi, Hamed Soren; Curvers, Katrien; Vleesschauwer, David; Delaere, Ilse; Aziz, Aziz; Höfte, Monica (The New phytologist, 2013)
Deficiency of abscisic acid (ABA) in the sitiens mutant of tomato (Solanum lycopersicum) culminates in increased resistance to Botrytis cinerea through a rapid epidermal hypersensitive response (HR) and associated phenylpropanoid pathway-derived cell wall fortifications. This study focused on understanding the role of primary carbon : nitrogen (C : N) metabolism in the resistance response of sitiens to B. cinerea. How alterations in C : N metabolism are linked with the HR-mediated epidermal arrest of the pathogen has been also investigated. Temporal alterations in the c-aminobutyric acid (GABA) shunt, glutamine synthetase/glutamate synthase (GS/GOGAT) cycle and phenylpropanoid pathway were transcriptionally, enzymatically and metabolically monitored in both wild-type and sitiens plants. Virus-induced gene silencing, microscopic analyses and pharmacological assays were used to further confirm the data. Our results on the sitiens–B. cinerea interaction favor a model in which cell viability in the cells surrounding the invaded tissue is maintained by a constant replenishment of the tricarboxylic acid (TCA) cycle through overactivation of the GS/GOGAT cycle and the GABA shunt, resulting in resistance through both tightly controlling the defense-associated HR and slowing down the pathogen-induced senescence. Collectively, this study shows that maintaining cell viability via alterations in host C : N metabolism plays a vital role in the resistance response against necrotrophic pathogens.